2020
DOI: 10.3390/diagnostics10010041
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Wave Elastography Variability Analysis and Relation with Kidney Allograft Dysfunction: A Single-Center Study

Abstract: Shear-wave elastography (SWE) showed the absence or presence of significant differences among stable kidney allograft function and allograft dysfunction. We evaluated the variability of kidney allograft stiffness in relation to allograft dysfunction, respectively, in terms of a correlation of stiffness with patients' characteristics. A single-center prospective study on patients who had undergone renal transplantation was conducted between October 2017 and November 2018. Patients were clinically classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…These discrepant findings have led the European Federation for Ultrasound in Medicine and Biology (EFSUMB) to point out that no definitive recommendations for the application of elastography in renal assessment can be made to date 24 . Most of the studies showed a positive correlation between stiffness parameters and fibrosis grades based on the assumption that as renal fibrosis progresses, the renal architecture becomes stiffer leading to faster propagation of the shear waves, which corresponds to higher elastography stiffness values 14,25,26,27,28,29 . Our findings stand in line with this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…These discrepant findings have led the European Federation for Ultrasound in Medicine and Biology (EFSUMB) to point out that no definitive recommendations for the application of elastography in renal assessment can be made to date 24 . Most of the studies showed a positive correlation between stiffness parameters and fibrosis grades based on the assumption that as renal fibrosis progresses, the renal architecture becomes stiffer leading to faster propagation of the shear waves, which corresponds to higher elastography stiffness values 14,25,26,27,28,29 . Our findings stand in line with this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…Although color Doppler is an established method to assess renal allografts, ultrasound elastography seems to show renal impairment earlier. Kidney stiffness has been used as a predictor of renal allograft fibrosis( 30 , 31 , 32 , 33 , 34 ). Renal sampling by SWE has been shown to have a reliability of 97.6% (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Elec et al [ 15 ] conducted a cross-sectional study of the early post-transplantation period and found that patients with delayed graft function showed lower values for wash-out area under the curve and wash-in and wash-out area under the curve in CEUS, which may be useful to diagnose delayed graft function. Using SWE, Bolboaca et al [ 16 ] identified the differences among stable graft function and graft dysfunction. It has been demonstrated that the cortical tissue stiffness provided significantly higher values for patients with graft dysfunction as compared to patients with stable function.…”
Section: Discussionmentioning
confidence: 99%